Restoration method of waste lithium iron phosphate and application thereof

Through hydrothermal lithium supplementation, polymerization coating and heat treatment, waste lithium iron phosphate is repaired, solving the problems of low recycling efficiency and high energy consumption in the existing technology, and achieving efficient and low energy consumption resource recycling and electrochemistry Performance improvement.

CN119430121APending Publication Date: 2025-02-14SHENZHEN INST OF ADVANCED TECH CHINESE ACAD OF SCI
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411692358.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

It is difficult to effectively recycle waste lithium iron phosphate in the prior art, and the commonly used repair methods have problems such as high energy consumption, long processes and a lot of pollutant discharge, which affects the recycling of resources and environmental protection.

Method used

The three-step method of hydrothermal lithium supplementation, polymerization coating and heat treatment is adopted to repair the waste lithium iron phosphate, achieving low energy consumption and high efficiency recovery, forming a uniform carbon coating layer, and improving the electrochemical performance of the material.

Benefits of technology

It realizes high-efficiency and low-energy recycling of waste lithium iron phosphate. The repaired material has excellent reversible discharge capacity and rate performance, reducing the preparation cost of lithium-ion batteries and making it more environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430121A_ABST
    Figure CN119430121A_ABST
Patent Text Reader

Abstract

The invention relates to a method for repairing waste lithium iron phosphate and application of the method, and belongs to the technical field of resource recovery. The repairing method comprises the following steps: S1, carrying out hydrothermal reaction on a mixture containing waste lithium iron phosphate, a reducing agent, a lithium source and water to obtain a precursor A; s2, mixing the precursor A with a polymer monomer solution to enable a polymer monomer to be polymerized and coated, and forming a polymer coating layer on the surface of the precursor A to obtain a precursor B; the polymer monomer comprises at least one of a polyphenol monomer, an acid monomer containing a sulfur heterocyclic ring or a monomer containing a carbon-carbon double bond; and S3, carrying out heat treatment on the precursor B in a protective gas atmosphere to obtain the repaired lithium iron phosphate material. According to the method disclosed by the invention, direct recovery of the waste lithium iron phosphate is realized through three steps of hydrothermal lithium supplementing, polymerization coating and heat treatment, and the recovered and repaired lithium iron phosphate material has high capacity and high rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of resource recovery, and in particular relates to a method for repairing waste lithium iron phosphate and an application thereof. Background Art

[0002] Lithium-ion batteries have promoted the widespread application of electricity in various fields of society and are widely used in electric vehicles, portable electronic devices, large-scale energy storage power stations and other fields. Along with this comes the problem of how to deal with a large number of scrapped lithium-ion batteries. If they cannot be effectively recycled, it will not only be a waste of resources, but also have a negative impact on the environment, deviating from people's beautiful expectations for a low-carbon society and a green environment, and will also have a negative impact on the waste of resources in the lithium-ion battery industry chain.

[0003] Lithium-ion batteries are composed of key components such as positive electrode, negative electrode, separator, current collector, electrolyte, etc. Most of the valuable metals are concentrated in the positive electrode material, so the recycling of positive electrode materials is a major task. The positive electrode materials of lithium-ion batteries are mainly divided into three categories: lithium iron phosphate, ternary positive electrode materials (LiTMO 2 , TM=Ni, Co, Mn, Al, etc.), lithium manganate. Among them, ternary cathode materials and lithium manganate materials contain high-priced transition metal materials such as nickel, cobalt and manganese, while the transition metal iron in lithium iron phosphate is relatively cheap. Therefore, the economic benefits of recycling lithium iron phosphate by conventional wet or pyrolysis are not as good as those of ternary materials and lithium manganate. Due to the rise of large-scale energy storage power stations and the increasing proportion of lithium iron phosphate in the electric vehicle industry, more and more lithium iron phosphate batteries are scrapped. Finding a low-cost and efficient recycling method for waste lithium iron phosphate will be beneficial to the environment and the healthy development of the lithium-ion battery industry.

[0004] The direct recycling method is a cathode-to-cathode recycling method that aims to repair the crystal composition and structure damage caused by electrochemical use and the electrochemical performance degradation caused by it through physical and chemical methods without destroying the crystal structure at the atomic level, and supplemented by surface repair means to restore the electrochemical performance of the failed cathode material to its initial state. Compared with wet recovery and pyrolysis recovery, this method has low energy consumption, short process and less pollution.

[0005] At present, the commonly used direct repair methods for waste lithium iron phosphate include hydrothermal method, high temperature solid phase method, etc. Among them, the hydrothermal method is to use an aqueous solution containing lithium salt or lithium hydroxide as a lithium supplement to supplement lithium-deficient waste lithium iron phosphate under high temperature and high pressure. Usually, this process requires a higher hydrothermal temperature, and the reaction needs to be carried out in an autoclave. In addition, lithium iron phosphate is usually coated with a layer of carbon layer on the surface to improve its conductivity. During the electrochemical cycle or in the pretreatment of waste batteries, the particles are broken or the original surface carbon layer is damaged to varying degrees, destroying its conductivity. Therefore, it is also necessary to repair the surface carbon layer while repairing lithium iron phosphate. For such problems, the usual practice is to dissolve the polymer in the solution, add lithium iron phosphate, stir and filter, thereby coating the polymer on the surface of the particles, and then obtain the surface carbon layer through a subsequent heat treatment process. However, this coating method is not easy to control, and it is easy to make the coating layer uneven, which is not conducive to the transmission of lithium ions. Summary of the invention

[0006] The present invention aims to solve one of the above-mentioned technical problems existing in the prior art. To this end, one of the purposes of the present invention is to provide a method for repairing waste lithium iron phosphate, which is based on a direct recovery method to repair the failed lithium iron phosphate, and achieves efficient and low-energy recovery of lithium iron phosphate materials. The hydrothermal temperature of the process is low, the process time is short, and a uniform carbon coating layer is achieved on the surface. The repaired lithium iron phosphate material has excellent rate performance.

[0007] A second object of the present invention is to provide a lithium iron phosphate material obtained by the above-mentioned repair method.

[0008] The third object of the present invention is to provide an application of the lithium iron phosphate material as mentioned above in the preparation of lithium ion batteries.

[0009] In order to achieve the above object, the technical solution adopted by the present invention is:

[0010] A first aspect of the present invention provides a method for repairing waste lithium iron phosphate, comprising the following steps:

[0011] S1, subjecting a mixture containing waste lithium iron phosphate, a reducing agent, a lithium source and water to a hydrothermal reaction to obtain a precursor A;

[0012] S2, mixing the precursor A with a polymer monomer solution, allowing the polymer monomer to undergo polymerization and coating, forming a polymer coating layer on the surface of the precursor A, and obtaining a precursor B; the polymer monomer comprises at least one of a polyphenol monomer, a sulfur-containing heterocyclic acid monomer, or a carbon-carbon double bond-containing monomer;

[0013] S3, heat-treating the precursor B in an atmosphere of protective gas to obtain a repaired lithium iron phosphate material.

[0014] The method for repairing waste lithium iron phosphate according to the first aspect of the present invention has at least the following beneficial effects:

[0015] The present invention realizes direct recovery of waste lithium iron phosphate through three steps of hydrothermal lithium replenishment, polymer coating and heat treatment. Firstly, a reducing agent and a lithium source are used to hydrothermally replenish waste lithium iron phosphate, and then a polymer monomer with a specific structure is used as a carbon source. By utilizing its polymerization characteristics, a uniform polymer coating layer is formed on the surface of the material. Finally, through a heat treatment process, further repair of the lithium iron phosphate crystal phase and uniform carbon layer coating on the surface are achieved, thereby completing the recovery and repair. The recovered and repaired lithium iron phosphate material has high capacity and high rate performance.

[0016] In some embodiments of the present invention, in step S1, the reducing agent includes at least one of a formic acid source, an oxalic acid source, thiourea or a carboxylic acid derivative.

[0017] In some embodiments of the present invention, in step S1, the lithium source includes at least one of lithium oxalate, lithium hydroxide, lithium carbonate, lithium chloride, lithium nitrate, lithium sulfate, lithium formate, lithium phosphate, lithium acetate, lithium metaphosphate or lithium borate.

[0018] In some embodiments of the present invention, in step S1, the oxalic acid source in the reducing agent includes at least one of oxalic acid, lithium oxalate, lithium hydrogen oxalate, sodium oxalate, sodium hydrogen oxalate, potassium oxalate, potassium hydrogen oxalate, ferrous oxalate, ammonium oxalate, ferric oxalate or hydrates of the above compounds.

[0019] The present invention uses a specific reducing agent and lithium source to achieve hydrothermal lithium replenishment at a relatively low temperature; in particular, the present invention uses lithium oxalate with reducing properties as a lithium replenishment agent, which can reduce the temperature of hydrothermal lithium replenishment to 100°C or below, and no high-voltage control device is required. In addition, if the added reducing agent and lithium source can eventually generate lithium oxalate, the repair effect on waste lithium iron phosphate is equivalent to adding lithium oxalate.

[0020] In some embodiments of the present invention, in step S1, the usage ratio of the waste lithium iron phosphate and water is a first solid-liquid ratio, and the first solid-liquid ratio is 0.01 to 15 g / mL.

[0021] The usage ratio of waste lithium iron phosphate and water, i.e. the first solid-liquid ratio, will have a certain influence on the lithium replenishment effect. Hydrothermal lithium replenishment under the first solid-liquid ratio within the specific range of the present invention can achieve a better lithium replenishment effect and effectively reduce the lithium replenishment cost.

[0022] In some embodiments of the present invention, in step S1, the reducing agent concentration in the mixture is 0.05 to 20 mol / L.

[0023] In some embodiments of the present invention, in step S1, the lithium ion concentration in the mixture is 0.1 to 40 mol / L.

[0024] The reducing agent concentration and lithium ion concentration in the mixture will have a certain impact on the lithium replenishment effect. Hydrothermal lithium replenishment under the reducing agent concentration and lithium ion concentration within the specific range of the present invention can achieve a better lithium replenishment effect and effectively reduce the lithium replenishment cost.

[0025] In some embodiments of the present invention, in step S1, the temperature of the hydrothermal reaction is 30-300°C.

[0026] In some embodiments of the present invention, in step S1, the hydrothermal reaction time is 0.5 to 200 hours.

[0027] The temperature and time of the hydrothermal reaction will have a certain influence on the lithium replenishment effect. Carrying out hydrothermal lithium replenishment under the temperature and time within the specific range of the present invention can achieve a better lithium replenishment effect and effectively reduce the lithium replenishment cost.

[0028] In some embodiments of the present invention, in step S2, the polyphenol monomers include diphenol monomers, pyrogallol monomers or a combination thereof; in some specific embodiments of the present invention, in step S2, the polyphenol monomers include at least one of dopamine, dopamine hydrochloride, catechol, catechin, ellagic acid, gallic acid, tannic acid or anthocyanidin.

[0029] In some embodiments of the present invention, in step S2, the sulfur-containing heterocyclic acid monomer is selected from dithiolane-containing acid monomers; in some specific embodiments of the present invention, in step S2, the sulfur-containing heterocyclic acid monomer includes α-lipoic acid, asparagus acid or a combination thereof.

[0030] In some embodiments of the present invention, in step S2, the carbon-carbon double bond-containing monomers include at least one of acrylic monomers, acrylonitrile monomers, acrylamide monomers, and ethylene monomers; in some specific embodiments of the present invention, in step S2, the carbon-carbon double bond-containing monomers include at least one of ethylene glycol methacrylate, 2-cyanoethyl acrylate, 2-cyanoacrylic acid, 2-cyanoacrylate propyl, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, acrylonitrile, N-isopropylacrylamide, N,N'-methylenebisacrylamide, 2-vinylpyridine, 3-vinylpyridine, 4-vinylpyridine, N-vinylformamide or N-vinylacetamide.

[0031] The polymer monomers will form different coating effects on the surface of the precursor A. The use of the specific type of polymer monomers of the present invention can form a more uniform coating effect on the surface of the precursor A, thereby achieving a better repair effect of the lithium iron phosphate and obtaining a lithium iron phosphate material with better reversible discharge capacity and rate performance.

[0032] In some embodiments of the present invention, in step S2, the concentration of the polymer monomer solution is 0.05-15 g / L.

[0033] The concentration of the polymer monomer solution will have a certain influence on the polymerization coating effect. Polymerization coating can be carried out at a concentration of the polymer monomer solution within a specific range of the present invention to achieve a better coating effect and effectively reduce the repair cost.

[0034] In some embodiments of the present invention, in step S2, the usage ratio of the precursor A to the polymer monomer solution is a second solid-liquid ratio, and the second solid-liquid ratio is 0.005-15 g / mL.

[0035] The dosage ratio of precursor A to polymer monomer solution, i.e., the second solid-liquid ratio, will have a certain influence on the polymerization coating effect. Polymerization coating can be carried out under the second solid-liquid ratio within the specific range of the present invention to achieve a better coating effect and effectively reduce the repair cost.

[0036] In some embodiments of the present invention, in step S2, the time for mixing the precursor A and the polymer monomer solution is 0.5 to 80 minutes.

[0037] The time of mixing the precursor A with the polymer monomer solution, i.e., the polymerization coating, will have a certain influence on the polymerization coating effect. Polymerization coating can achieve a better coating effect and effectively reduce the repair cost by mixing the precursor A with the polymer monomer solution, i.e., the polymerization coating can be carried out within the specific range of the mixing time of the present invention.

[0038] In some specific embodiments of the present invention, in step S2, the average thickness of the polymer coating layer is ≤20 nm.

[0039] Through step S2 of the present invention, a uniform polymer coating thin layer can be formed on the surface of the lithium iron phosphate particles.

[0040] In some embodiments of the present invention, in step S3, the protective gas includes an inert gas, a reducing gas or a combination thereof.

[0041] In some embodiments of the present invention, in step S3, the temperature of the heat treatment is 200-900°C.

[0042] In some embodiments of the present invention, in step S3, the heat treatment is carried out for a holding time of 0.5 to 15 hours.

[0043] The temperature and holding time of heat treatment will have a certain impact on the repair of lithium iron phosphate crystal phase and the uniformity of carbon layer coating. Heat treatment under the temperature and holding time within the specific range of the present invention can achieve better repair effect and effectively reduce the repair cost.

[0044] The second aspect of the present invention provides a lithium iron phosphate material obtained by the repair method described in the first aspect of the present invention.

[0045] The lithium iron phosphate material according to the second aspect of the present invention has at least the following beneficial effects:

[0046] The repair method of the present invention is simple and efficient, and the obtained lithium iron phosphate material has a complete crystalline phase structure and a uniform surface carbon coating layer, and has excellent electrochemical properties such as reversible discharge capacity and rate performance.

[0047] In some embodiments of the present invention, the lithium iron phosphate material includes lithium iron phosphate particles and a carbon coating layer coated on at least a portion of the surface of the lithium iron phosphate particles.

[0048] In some embodiments of the present invention, the average thickness of the carbon coating layer is ≤15 nm.

[0049] The third aspect of the present invention provides a use of the lithium iron phosphate material as described in the second aspect of the present invention in the preparation of a lithium ion battery.

[0050] The application according to the third aspect of the present invention has at least the following beneficial effects:

[0051] The lithium iron phosphate material obtained in the second aspect of the present invention is prepared into a lithium ion battery, which can obtain excellent electrochemical properties, such as excellent reversible discharge capacity and rate performance; and because the lithium iron phosphate material is obtained by repairing waste lithium iron phosphate, the repair process is simple and the repair effect is good, which is conducive to reducing the preparation cost of lithium ion batteries and is more environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 It is a technical route flow chart of the method for repairing waste lithium iron phosphate in an embodiment of the present invention.

[0053] Figure 2 This is a transmission electron microscope image of the polymer monomer after polymerization and coating of lithium iron phosphate in Example 1 of the present invention.

[0054] Figure 3 It is a comparison chart of the rate performance of Example 1 of the present invention and Comparative Example 1.

[0055] Figure 4 The cycle performance of the lithium iron phosphate material obtained in Example 1 of the present invention at 5C and 10C rates. DETAILED DESCRIPTION

[0056] The following is a detailed description of the embodiments of the present invention, which are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. The term "comprising" and other equivalent descriptions involved in the specification and claims of this application are intended to cover non-exclusive inclusions, including both the contents clearly described in the specification and claims and the steps or units that are not described in the specification and claims but are inherent in the product, method or structure.

[0057] The first aspect of the embodiment of the present invention provides a method for repairing waste lithium iron phosphate, the technical route flow chart is as follows: Figure 1 As shown, the following steps are included:

[0058] S1, subjecting a mixture containing waste lithium iron phosphate, a reducing agent, a lithium source and water to a hydrothermal reaction to obtain a precursor A;

[0059] S2, mixing the precursor A with the polymer monomer solution, polymerizing and coating the polymer monomer to form a polymer coating layer on the surface of the precursor A, and obtaining the precursor B; the polymer monomer comprises at least one of a polyphenol monomer, a sulfur-containing heterocyclic acid monomer or a carbon-carbon double bond-containing monomer;

[0060] S3. Heat-treating the precursor B in an atmosphere of protective gas to obtain a repaired lithium iron phosphate material.

[0061] The present invention realizes direct recovery of waste lithium iron phosphate through three steps of hydrothermal lithium replenishment, polymer coating and heat treatment. Firstly, a reducing agent and a lithium source are used to hydrothermally replenish waste lithium iron phosphate, and then a polymer monomer with a specific structure is used as a carbon source. By utilizing its polymerization characteristics, a uniform polymer coating layer is formed on the surface of the material. Finally, through a heat treatment process, further repair of the lithium iron phosphate crystal phase and uniform carbon layer coating on the surface are achieved, thereby completing the recovery and repair. The recovered and repaired lithium iron phosphate material has high capacity and high rate performance.

[0062] In some embodiments of the present invention, in step S1, the waste lithium iron phosphate comes from waste lithium ion batteries; in some specific embodiments of the present invention, in step S1, the waste lithium iron phosphate comes from the positive electrode of waste lithium ion batteries, especially the lithium iron phosphate positive electrode.

[0063] In some embodiments of the present invention, in step S1, the reducing agent and the lithium source may be the same or different. If a substance has reducing properties and can also provide a lithium source, then the reducing agent and the lithium source in the present invention may be the substance.

[0064] In some embodiments of the present invention, in step S1, the reducing agent is a water-soluble reducing agent, and the lithium source is a water-soluble lithium source.

[0065] In some embodiments of the present invention, in step S1, the reducing agent includes at least one of a formic acid source, an oxalic acid source, thiourea or a carboxylic acid derivative; in some specific embodiments of the present invention, in step S1, the reducing agent includes a formic acid source, an oxalic acid source or a combination thereof; in some examples of the present invention, in step S1, the reducing agent is selected from an oxalic acid source.

[0066] In some embodiments of the present invention, the carboxylic acid derivative comprises at least one of an acyl halide, an anhydride, an ester or an amide.

[0067] In some embodiments of the present invention, in step S1, the oxalic acid source in the reducing agent includes at least one of oxalic acid, lithium oxalate, lithium hydrogen oxalate, sodium oxalate, sodium hydrogen oxalate, potassium oxalate, potassium hydrogen oxalate, ferrous oxalate, ammonium oxalate, ferric oxalate or hydrates of the above compounds; in some embodiments of the present invention, in step S1, the oxalic acid source in the reducing agent includes at least one of anhydrous oxalic acid, dihydrate oxalic acid, lithium oxalate, sodium oxalate, potassium oxalate, potassium hydrogen oxalate, ferrous oxalate or ferric oxalate.

[0068] In some embodiments of the present invention, in step S1, the lithium source includes at least one of lithium oxalate, lithium hydroxide, lithium carbonate, lithium chloride, lithium nitrate, lithium sulfate, lithium formate, lithium phosphate, lithium acetate, lithium metaphosphate or lithium borate; in some specific embodiments of the present invention, in step S1, the lithium source includes at least one of lithium oxalate, lithium hydroxide, lithium carbonate, lithium chloride, lithium sulfate, lithium formate, lithium phosphate, lithium acetate, lithium metaphosphate or lithium borate.

[0069] In some embodiments of the present invention, in step S1, the reducing agent and the lithium source are both selected from lithium oxalate.

[0070] The present invention uses a specific reducing agent and lithium source to achieve hydrothermal lithium replenishment at a relatively low temperature; in particular, the present invention uses lithium oxalate with reducing properties as a lithium replenishment agent, which can reduce the temperature of hydrothermal lithium replenishment to 100°C or below, and no high-voltage control device is required. In addition, if the added reducing agent and lithium source can eventually generate lithium oxalate, the repair effect on waste lithium iron phosphate is equivalent to adding lithium oxalate.

[0071] In some embodiments of the present invention, in step S1, the ratio of waste lithium iron phosphate to water is a first solid-liquid ratio, and the first solid-liquid ratio is 0.01-15 g / mL; in some specific embodiments of the present invention, the first solid-liquid ratio is 0.03-12 g / mL; in some examples of the present invention, the first solid-liquid ratio is 0.05-10 g / mL. Non-limiting specific examples include 0.05 g / mL, 0.1 g / mL, 0.2 g / mL, 0.5 g / mL, 1 g / mL, 2 g / mL, 3 g / mL, 5 g / mL, and 10 g / mL.

[0072] The usage ratio of waste lithium iron phosphate and water, i.e. the first solid-liquid ratio, will have a certain influence on the lithium replenishment effect. Hydrothermal lithium replenishment under the first solid-liquid ratio within the specific range of the present invention can achieve a better lithium replenishment effect and effectively reduce the lithium replenishment cost.

[0073] In some embodiments of the present invention, in step S1, the reducing agent concentration in the mixture is 0.05-20 mol / L; in some specific embodiments of the present invention, in step S1, the reducing agent concentration in the mixture is 0.08-18 mol / L; in some examples of the present invention, in step S1, the reducing agent concentration in the mixture is 0.1-15 mol / L. Non-limiting specific examples include 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.5 mol / L, 0.8 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 5 mol / L, 8 mol / L, 10 mol / L, 12 mol / L, and 15 mol / L.

[0074] In some embodiments of the present invention, in step S1, the lithium ion concentration in the mixture is 0.1-40 mol / L; in some specific embodiments of the present invention, in step S1, the lithium ion concentration in the mixture is 0.16-36 mol / L; in some examples of the present invention, in step S1, the lithium ion concentration in the mixture is 0.2-30 mol / L. Non-limiting specific examples include 0.2 mol / L, 0.4 mol / L, 0.6 mol / L, 1 mol / L, 1.6 mol / L, 2 mol / L, 4 mol / L, 6 mol / L, 10 mol / L, 16 mol / L, 20 mol / L, 24 mol / L, and 30 mol / L.

[0075] The reducing agent concentration and lithium ion concentration in the mixture will have a certain impact on the lithium replenishment effect. Hydrothermal lithium replenishment under the reducing agent concentration and lithium ion concentration within the specific range of the present invention can achieve a better lithium replenishment effect and effectively reduce the lithium replenishment cost.

[0076] In some embodiments of the present invention, in step S1, the temperature of the hydrothermal reaction is 30-300°C; in some specific embodiments of the present invention, in step S1, the temperature of the hydrothermal reaction is 40-280°C; in some examples of the present invention, in step S1, the temperature of the hydrothermal reaction is 50-250°C. Non-limiting specific examples include 50°C, 60°C, 80°C, 100°C, 120°C, 140°C, 160°C, 180°C, 200°C, 220°C, and 250°C.

[0077] In some embodiments of the present invention, in step S1, the time of the hydrothermal reaction is 0.5 to 200 hours; in some specific embodiments of the present invention, in step S1, the time of the hydrothermal reaction is 0.8 to 180 hours; in some examples of the present invention, in step S1, the time of the hydrothermal reaction is 1 to 168 hours. Non-limiting specific examples include 1 hour, 2 hours, 4 hours, 6 hours, 9 hours, 12 hours, 18 hours, 24 hours, 48 ​​hours, 72 hours, 96 hours, 120 hours, 144 hours, and 168 hours.

[0078] The temperature and time of the hydrothermal reaction will have a certain influence on the lithium replenishment effect. Carrying out hydrothermal lithium replenishment under the temperature and time within the specific range of the present invention can achieve a better lithium replenishment effect and effectively reduce the lithium replenishment cost.

[0079] In some embodiments of the present invention, in step S2, the polyphenol monomers include diphenol monomers, pyrogallol monomers or a combination thereof; in some specific embodiments of the present invention, in step S2, the polyphenol monomers include at least one of dopamine, dopamine hydrochloride, catechol, catechin, ellagic acid, gallic acid, tannic acid or anthocyanidin; in some examples of the present invention, in step S2, the polyphenol monomers include at least one of tannic acid, dopamine, dopamine hydrochloride, catechol, catechin or anthocyanidin; in some specific examples of the present invention, in step S2, the polyphenol monomers include at least one of tannic acid, dopamine, dopamine hydrochloride, catechol, catechin or anthocyanidin.

[0080] In some embodiments of the present invention, in step S2, the sulfur-containing heterocyclic acid monomer is selected from dithiolane-containing acid monomers; in some specific embodiments of the present invention, in step S2, the sulfur-containing heterocyclic acid monomer includes α-lipoic acid, asparagus acid or a combination thereof; in some examples of the present invention, the sulfur-containing heterocyclic acid monomer is selected from α-lipoic acid.

[0081] In some embodiments of the present invention, in step S2, the monomers containing carbon-carbon double bonds include at least one of acrylic monomers, acrylonitrile monomers, acrylamide monomers, and vinyl monomers; in some specific embodiments of the present invention, in step S2, the monomers containing carbon-carbon double bonds include at least one of acetyl-containing acrylic monomers, cyano-containing acrylic monomers, hydroxyl-containing acrylic monomers, acrylonitrile monomers, acrylamide monomers, nitrogen-containing heterocyclic vinyl monomers, or amide-containing vinyl monomers; in some examples of the present invention, in step S2, the monomers containing carbon-carbon double bonds include at least one of acetyl-containing acrylic monomers, cyano-containing acrylic monomers, or hydroxyl-containing acrylic monomers.

[0082] In the present invention, the carbon-carbon double bond-containing monomers can achieve good polymerization coating effects; in particular, the polymerization coating effects of acetyl-containing acrylic monomers, cyano-containing acrylic monomers and hydroxyl-containing acrylic monomers are better.

[0083] In some embodiments of the present invention, in step S2, the carbon-carbon double bond-containing monomer includes at least one of ethylene glycol methacrylate acetoacetate, 2-cyanoethyl acrylate, 2-cyanoacrylic acid, propyl 2-cyanoacrylate, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, acrylonitrile, N-isopropylacrylamide, N,N'-methylenebisacrylamide, 2-vinylpyridine, 3-vinylpyridine, 4-vinylpyridine, N-vinylformamide or N-vinylacetamide; In some specific embodiments of the present invention, in step S2, the carbon-carbon double bond-containing monomer includes at least one of ethylene glycol methacrylate acetoacetate, 2-cyanoethyl acrylate, hydroxyethyl methacrylate, acrylonitrile, N-isopropylacrylamide, 4-vinylpyridine or N-vinylformamide; In some examples of the present invention, in step S2, the carbon-carbon double bond-containing monomer includes at least one of ethylene glycol methacrylate acetoacetate, 2-cyanoethyl acrylate or hydroxyethyl methacrylate.

[0084] In some embodiments of the present invention, in step S2, the polymer monomer includes tannic acid, dopamine, dopamine hydrochloride, gallic acid, ellagic acid, catechol, catechin, anthocyanin, α-lipoic acid, asparagus acid, ethylene glycol methacrylate, 2-cyanoethyl acrylate, 2-cyanoacrylic acid, 2-cyanoacrylate propyl, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, acrylonitrile, N-isopropylacrylamide, N,N'-methylenebisacrylamide, 2-vinylpyridine, 3-vinylpyridine, 4-vinylpyridine, N-vinylformamide or N-vinylethyl amide; in some specific embodiments of the present invention, in step S2, the polymer monomer includes at least one of tannic acid, dopamine, dopamine hydrochloride, α-lipoic acid, ethylene glycol methacrylate, 2-cyanoethyl acrylate, hydroxyethyl methacrylate, acrylonitrile, N-isopropylacrylamide, 4-vinylpyridine or N-vinylformamide; in some specific embodiments of the present invention, in step S2, the polymer monomer includes at least one of tannic acid, dopamine, dopamine hydrochloride, α-lipoic acid, ethylene glycol methacrylate, 2-cyanoethyl acrylate or hydroxyethyl methacrylate.

[0085] The polymer monomers will form different coating effects on the surface of the precursor A. The use of the specific type of polymer monomers of the present invention can form a more uniform coating effect on the surface of the precursor A, thereby achieving a better repair effect of the lithium iron phosphate and obtaining a lithium iron phosphate material with better reversible discharge capacity and rate performance.

[0086] In some embodiments of the present invention, in step S2, the concentration of the polymer monomer solution is 0.05-15 g / L; in some specific embodiments of the present invention, in step S2, the concentration of the polymer monomer solution is 0.08-12 g / L; in some examples of the present invention, in step S2, the concentration of the polymer monomer solution is 0.1-10 g / L. Non-limiting specific examples include 0.1 g / L, 0.2 g / L, 0.5 g / L, 0.8 g / L, 1 g / L, 2 g / L, 5 g / L, 8 g / L, and 10 g / L.

[0087] The concentration of the polymer monomer solution will have a certain influence on the polymerization coating effect. Polymerization coating can be carried out at a concentration of the polymer monomer solution within a specific range of the present invention to achieve a better coating effect and effectively reduce the repair cost.

[0088] In some embodiments of the present invention, in step S2, the amount ratio of precursor A to polymer monomer solution is a second solid-liquid ratio, and the second solid-liquid ratio is 0.005-15 g / mL; in some specific embodiments of the present invention, the second solid-liquid ratio is 0.008-12 g / mL; in some examples of the present invention, the second solid-liquid ratio is 0.01-10 g / mL. Non-limiting specific examples include 0.01 g / mL, 0.05 g / mL, 0.1 g / mL, 0.2 g / mL, 0.5 g / mL, 0.8 g / mL, 1 g / mL, 2 g / mL, 5 g / mL, 8 g / mL, and 10 g / mL.

[0089] The dosage ratio of precursor A to polymer monomer solution, i.e., the second solid-liquid ratio, will have a certain influence on the polymerization coating effect. Polymerization coating can be carried out under the second solid-liquid ratio within the specific range of the present invention to achieve a better coating effect and effectively reduce the repair cost.

[0090] In some embodiments of the present invention, in step S2, the time for mixing the precursor A with the polymer monomer solution is 0.5 to 80 minutes; in some specific embodiments of the present invention, in step S2, the time for mixing the precursor A with the polymer monomer solution is 0.8 to 70 minutes; in some examples of the present invention, in step S2, the time for mixing the precursor A with the polymer monomer solution is 1 to 60 minutes. Non-limiting specific examples include 1 minute, 2 minutes, 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes, and 60 minutes.

[0091] The time of mixing the precursor A with the polymer monomer solution, i.e., the polymerization coating, will have a certain influence on the polymerization coating effect. Polymerization coating can achieve a better coating effect and effectively reduce the repair cost by mixing the precursor A with the polymer monomer solution, i.e., the polymerization coating can be carried out within the specific range of the mixing time of the present invention.

[0092] In some embodiments of the present invention, in step S2, the average thickness of the polymer coating layer is ≤20nm; in some specific embodiments of the present invention, in step S2, the average thickness of the polymer coating layer is 0.1-20nm; in some examples of the present invention, in step S2, the average thickness of the polymer coating layer is 1-15nm. Non-limiting specific examples include 1nm, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, and 15nm.

[0093] After step S2 in the embodiment of the present invention, a uniform polymer coating thin layer can be formed on the surface of the lithium iron phosphate particles.

[0094] In some embodiments of the present invention, in step S3, the protective gas includes an inert gas, a reducing gas or a combination thereof; in some specific embodiments of the present invention, in step S3, the protective gas includes at least one of argon, nitrogen, helium, neon, krypton, carbon dioxide, carbon monoxide or hydrogen; in some examples of the present invention, in step S3, the protective gas includes one of argon, nitrogen, carbon dioxide, helium, neon, krypton, a hydrogen-argon mixture or carbon monoxide.

[0095] In some embodiments of the present invention, in step S3, the temperature of the heat treatment is 200-900°C; in some specific embodiments of the present invention, in step S3, the temperature of the heat treatment is 250-850°C; in some examples of the present invention, in step S3, the temperature of the heat treatment is 300-800°C. Non-limiting specific examples include 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, and 800°C.

[0096] In some embodiments of the present invention, in step S3, the heat treatment holding time is 0.5 to 15 hours; in some specific embodiments of the present invention, in step S3, the heat treatment holding time is 0.8 to 12 hours; in some examples of the present invention, in step S3, the heat treatment holding time is 1 to 10 hours. Non-limiting specific examples include 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, and 10 hours.

[0097] The temperature and holding time of heat treatment will have a certain impact on the repair of lithium iron phosphate crystal phase and the uniformity of carbon layer coating. Heat treatment under the temperature and holding time within the specific range of the present invention can achieve better repair effect and effectively reduce the repair cost.

[0098] A second aspect of the embodiments of the present invention provides a lithium iron phosphate material obtained by the repair method of the first aspect of the embodiments of the present invention.

[0099] The repair method in the embodiment of the present invention is simple and efficient, and the obtained lithium iron phosphate material has a complete crystalline phase structure and a uniform surface carbon coating layer, and has excellent electrochemical properties such as reversible discharge capacity and rate performance.

[0100] In some embodiments of the present invention, the lithium iron phosphate material includes lithium iron phosphate particles and a carbon coating layer coated on at least a portion of the surface of the lithium iron phosphate particles.

[0101] In some embodiments of the present invention, the average thickness of the carbon coating layer is ≤15nm; in some specific embodiments of the present invention, the average thickness of the carbon coating layer is 0.1-15nm; in some examples of the present invention, the average thickness of the carbon coating layer is 1-10nm. Non-limiting specific examples include 1nm, 2nm, 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, and 10nm.

[0102] A third aspect of the embodiments of the present invention provides a use of the lithium iron phosphate material as described in the second aspect of the embodiments of the present invention in the preparation of a lithium ion battery.

[0103] The lithium iron phosphate material obtained in the second aspect of the embodiment of the present invention is prepared into a lithium ion battery, which can obtain excellent electrochemical properties, such as excellent reversible discharge capacity and rate performance; and because the lithium iron phosphate material is obtained by repairing waste lithium iron phosphate, the repair process is simple and the repair effect is good, which is conducive to reducing the preparation cost of lithium ion batteries and is more green and environmentally friendly.

[0104] In some embodiments of the present invention, a lithium-ion battery includes a positive electrode, a negative electrode, and an electrolyte.

[0105] In some embodiments of the present invention, lithium iron phosphate material is used to prepare a positive electrode of a lithium-ion battery.

[0106] In some embodiments of the present invention, raw materials for preparing the positive electrode of the lithium-ion battery include: a conductive agent, a binder, and the lithium iron phosphate material of the second aspect of the embodiments of the present invention.

[0107] In some embodiments of the present invention, the conductive agent includes at least one of conductive carbon, acetylene black, carbon nanotubes or graphene; in some specific embodiments of the present invention, the conductive agent includes conductive carbon, acetylene black or a combination thereof; in some examples of the present invention, the conductive agent is selected from conductive carbon.

[0108] In some embodiments of the present invention, the binder includes at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyacrylic acid, polyacrylonitrile, carboxymethyl cellulose, polymethyl methacrylate, styrene-butadiene rubber or polyvinyl alcohol; in some specific embodiments of the present invention, the binder includes at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyacrylic acid or polyacrylonitrile; in some examples of the present invention, the binder is selected from polytetrafluoroethylene (PTFE).

[0109] In some embodiments of the present invention, the mass ratio of lithium iron phosphate material to conductive agent is 1: (0.01-1); in some specific embodiments of the present invention, the mass ratio of lithium iron phosphate material to conductive agent is 1: (0.05-0.5); in some examples of the present invention, the mass ratio of lithium iron phosphate material to conductive agent is 1: (0.1-0.3). Non-limiting specific examples are 1: 0.1, 1: 0.125, 1: 0.15, 1: 0.2, 1: 0.25 or 1: 0.3.

[0110] In some embodiments of the present invention, the mass ratio of lithium iron phosphate material to binder is 1:(0.01-1); in some specific embodiments of the present invention, the mass ratio of lithium iron phosphate material to binder is 1:(0.05-0.5); in some examples of the present invention, the mass ratio of lithium iron phosphate material to binder is 1:(0.1-0.3). Non-limiting specific examples include 1:0.1, 1:0.125, 1:0.15, 1:0.2, 1:0.25 or 1:0.3.

[0111] In some embodiments of the present invention, the negative electrode of the lithium-ion battery is selected from lithium.

[0112] In some embodiments of the present invention, the electrolyte of the lithium-ion battery is selected from liquid electrolytes.

[0113] In some embodiments of the present invention, the liquid electrolyte includes an electrolyte salt and a solvent; in some specific embodiments of the present invention, the electrolyte salt is selected from lithium salts; and the solvent includes an ester solvent, an ether solvent, or a combination thereof.

[0114] In some embodiments of the present invention, the concentration of the electrolyte salt in the liquid electrolyte is 0.5-2 mol / L; in some specific embodiments of the present invention, the concentration of the electrolyte salt in the liquid electrolyte is 0.8-1.2 mol / L; non-limiting specific examples are 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.1 mol / L or 1.2 mol / L.

[0115] In some embodiments of the present invention, the lithium salt in the liquid electrolyte includes LiPF 6 、LiFSI、LiTFSI、LiBF 4 , LiBOB or LiDFOB; in some specific embodiments of the present invention, the liquid electrolyte includes a lithium salt including LiPF 6 , LiFSI or LiTFSI; in some examples of the present invention, the liquid electrolyte, the lithium salt is selected from LiPF 6 .

[0116] In some embodiments of the present invention, in the liquid electrolyte, the solvent includes at least one of ethylene glycol dimethyl ether (DME), dioxolane (DOL), propylene carbonate (PC), ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC) or ethyl methyl carbonate (EMC); in some specific embodiments of the present invention, in the liquid electrolyte, the solvent includes at least one of ethylene carbonate (EC), dimethyl carbonate (DMC) or ethyl methyl carbonate (EMC); in some examples of the present invention, in the liquid electrolyte, the solvent includes ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC).

[0117] In some embodiments of the present invention, in the solvent of the liquid electrolyte, the volume ratio of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) is 1:(0.5-2):(0.5-2); non-limiting specific examples are 1:0.5:0.5, 1:0.5:1, 1:1:1, 1:1.5:0.5, 1:1.5:1.5 or 1:2:2.

[0118] In some embodiments of the present invention, the lithium-ion battery further comprises a battery separator; in some specific embodiments of the present invention, the battery separator is selected from glass fiber.

[0119] The content of the present invention is further described in detail below through specific examples. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the principles set forth in the present invention all belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific data exemplified below. The raw materials, reagents or devices used in the following examples, unless otherwise specified, can all be obtained from conventional commercial sources, or can be obtained by existing known methods.

[0120] In the following examples and comparative examples, the waste lithium iron phosphate used comes from waste lithium iron phosphate batteries or waste lithium iron phosphate pole pieces from battery factories.

[0121] Example 1

[0122] A method for repairing waste lithium iron phosphate, the specific steps are as follows:

[0123] S1: Using lithium oxalate as the oxalic acid source (reducing agent) and lithium source, waste lithium iron phosphate and 0.2 mol / L lithium oxalate aqueous solution are added into a flask (equipped with a condensation reflux device) at a solid-liquid ratio of 1 to 0.2 g / mL, maintained at 100°C for 4 hours, and filtered after cooling to obtain precursor A;

[0124] S2: Precursor A and 5 g / L tannic acid solution were stirred at room temperature at a solid-liquid ratio of 2 to 0.1 g / mL for 15 min, filtered, and dried to obtain precursor B;

[0125] S3: Heat the precursor B to 600° C. in an argon atmosphere, keep the temperature for 4 hours, and then cool down to obtain the repaired lithium iron phosphate material.

[0126] Embodiments 2 to 8

[0127] A method for repairing waste lithium iron phosphate, which differs from Example 1 in that the concentration of lithium oxalate in step S1 is changed, and the specific concentration is shown in Table 1; other raw materials and preparation steps are the same as those in Example 1.

[0128] Embodiments 9 to 15

[0129] A method for repairing waste lithium iron phosphate, which differs from Example 1 in that the type of oxalic acid source added in step S1 is changed, the specific type of oxalic acid source is shown in Table 1, and the oxalate concentration is controlled to be 0.3 mol / L; other raw materials and preparation steps are the same as those in Example 1.

[0130] Examples 16 to 24

[0131] A method for repairing waste lithium iron phosphate, which differs from Example 1 in that the type of lithium source added in step S1 is changed, the specific type of lithium source is shown in Table 1, and the lithium ion concentration is controlled to be 0.5 mol / L; other raw materials and preparation steps are the same as those in Example 1.

[0132] Embodiments 25 to 34

[0133] A method for repairing waste lithium iron phosphate, which differs from Example 1 in that the hydrothermal temperature in step S1 is changed, the specific hydrothermal temperature is shown in Table 1, and when the hydrothermal temperature is higher than 100°C, the reaction vessel is replaced with a hydrothermal reactor; the raw materials and other preparation steps are the same as those in Example 1.

[0134] Embodiments 35 to 47

[0135] A method for repairing waste lithium iron phosphate is different from Example 1 in that the hydrothermal time in step S1 is changed, and the specific hydrothermal time is shown in Table 1; the raw materials and other preparation steps are the same as those in Example 1.

[0136] Embodiments 48 to 53

[0137] A method for repairing waste lithium iron phosphate is different from Example 1 in that the solid-liquid ratio 1 in step S1 is changed, and the specific solid-liquid ratio 1 is shown in Table 1; other raw materials and preparation steps are the same as those in Example 1.

[0138] Embodiments 54 to 63

[0139] A method for repairing waste lithium iron phosphate, which differs from Example 1 in that the type of polymer monomer in step S2 is changed, and the specific polymer monomer type is shown in Table 1; other raw materials and preparation steps are the same as those in Example 1.

[0140] Embodiments 64 to 69

[0141] A method for repairing waste lithium iron phosphate, which is different from Example 1 in that the concentration of polymer small molecules in step S2 is changed, and the specific polymer small molecule concentration is shown in Table 1; other raw materials and preparation steps are the same as Example 1.

[0142] Embodiments 70 to 75

[0143] A method for repairing waste lithium iron phosphate, which differs from Example 1 in that the solid-liquid ratio 2 in step S2 is changed, and the specific solid-liquid ratio 2 is shown in Table 1; other raw materials and preparation steps are the same as those in Example 1.

[0144] Embodiments 76 to 84

[0145] A method for repairing waste lithium iron phosphate is different from that of Example 1 in that the stirring time in step S2 is changed, and the specific stirring time is shown in Table 1; the raw materials and other preparation steps are the same as those of Example 1.

[0146] Embodiments 85 to 94

[0147] A method for repairing waste lithium iron phosphate is different from Example 1 in that the heat treatment temperature in step S3 is changed, and the specific heat treatment temperature is shown in Table 1; the raw materials and other preparation steps are the same as those in Example 1.

[0148] Examples 95 to 102

[0149] A method for repairing waste lithium iron phosphate, which differs from Example 1 in that the heat treatment atmosphere in step S3 is changed, and the specific heat treatment atmosphere is shown in Table 1; other raw materials and preparation steps are the same as those in Example 1.

[0150] Embodiments 103 to 111

[0151] A method for repairing waste lithium iron phosphate is different from Example 1 in that the heat treatment time in step S3 is changed, and the specific heat treatment time is shown in Table 1; the raw materials and other preparation steps are the same as those in Example 1.

[0152] Embodiments 112-113

[0153] A method for repairing waste lithium iron phosphate, which differs from Example 1 in that the types of oxalic acid source and lithium source in step S1 are changed, as shown in Table 1; the other preparation steps are the same as those in Example 1.

[0154] Table 1 Experimental conditions of Examples 1 to 113

[0155]

[0156]

[0157]

[0158]

[0159]

[0160]

[0161] Comparative Example 1

[0162] A lithium iron phosphate material, specifically commercially available lithium iron phosphate (purchased from Shenzhen Defang Nano Technology Co., Ltd.).

[0163] Comparative Example 2

[0164] A lithium iron phosphate material, specifically untreated waste lithium iron phosphate.

[0165] Comparative Example 3

[0166] A method for repairing waste lithium iron phosphate, which differs from Example 1 in that this example is only processed by step S1 in Example 1, and steps S2 and S3 are not performed; that is, the precursor A obtained by step S1 is the repaired lithium iron phosphate material in this example.

[0167] Comparative Example 4

[0168] A method for repairing waste lithium iron phosphate is different from Example 1 in that this example only undergoes step S3 processing in Example 1, and does not perform steps S1 and S2 processing; that is, in this example, the waste lithium iron phosphate is directly processed in step S3.

[0169] Comparative Example 5

[0170] A method for repairing waste lithium iron phosphate, which differs from Example 1 in that this example only undergoes steps S1 and S2 in Example 1, and does not undergo step S3; that is, the precursor B obtained after steps S1 and S2 is the repaired lithium iron phosphate material in this example.

[0171] Comparative Example 6

[0172] A method for repairing waste lithium iron phosphate is different from Example 1 in that this example only undergoes steps S1 and S3 in Example 1, and does not undergo step S2; that is, in this example, precursor A is obtained through step S1, and precursor A is directly subjected to heat treatment in step S3.

[0173] Comparative Example 7

[0174] A method for repairing waste lithium iron phosphate, which differs from Example 1 in that this example only undergoes steps S2 and S3 in Example 1, and does not undergo step S1; that is, in this example, the waste lithium iron phosphate is directly mixed with a tannic acid solution, and steps S2 and S3 are performed.

[0175] Performance Testing

[0176] 1) Morphology characterization: The materials obtained in the examples and comparative examples were characterized using a transmission electron microscope. Figure 2 This is a transmission electron microscope image of the polymer monomers after polymerization and coating of lithium iron phosphate in Example 1 of the present invention. It can be seen from the image that the method of Example 1 can form a uniform polymer coating layer on the surface of lithium iron phosphate particles.

[0177] 2) The lithium iron phosphate materials obtained in Examples 1 to 112 and Comparative Examples 1 to 7 were uniformly mixed with conductive carbon and PTFE binder in a mass ratio of 8:1:1 to make positive electrode sheets, assembled into batteries, and the electrochemical performance was tested. The negative electrode of the battery was metallic lithium, the diaphragm was glass fiber, and the electrolyte was: 1M LiPF 6 (EC: DMC: EMC = 1:1:1). The constant current charge and discharge test uses a commercially available battery tester in a constant temperature and humidity room (25°C, 35%), and the positive electrode loading of the battery is 2-4 mg / cm 2 , the battery charge and discharge current density is 1C = 170mA / g, and the initial upper and lower limits of the test voltage are set to 2.2V and 3.8V. The test results are shown in Table 2.

[0178] Table 2 Performance test results of lithium iron phosphate materials obtained in Examples 1 to 113 and Comparative Examples 1 to 7

[0179]

[0180]

[0181]

[0182]

[0183] It can be seen from Table 1 and Table 2 that the lithium iron phosphate material repaired in the embodiment of the present invention and the lithium ion half-cell assembled with the matching electrolyte have obtained good reversible discharge capacity and high rate performance. The specific analysis is as follows:

[0184] In Examples 1 to 8, different concentrations of lithium oxalate solutions were used to supplement waste lithium iron phosphate. It was found that as the concentration of the lithium oxalate solution increased, the performance of the lithium iron phosphate after supplementation increased. When the concentration reached a certain level, further increase in the concentration had no significant effect on the performance of the lithium iron phosphate. Considering the cost and the effect of supplementation, the comprehensive effect was better when the concentration of the lithium oxalate solution was 0.2 mol / L.

[0185] In Example 1 and Examples 9 to 15, only the type of oxalic acid source added was changed, and it was found that the performance of the repaired lithium iron phosphate was not much different;

[0186] In Example 1 and Examples 16 to 24, only the type of lithium source added was changed, and it was found that the performance of the repaired lithium iron phosphate was not much different;

[0187] In Example 1 and Examples 25 to 34, only the lithium replenishment temperature was changed. It was found that as the lithium replenishment temperature increased, the performance of the lithium iron phosphate after lithium replenishment increased. After reaching a certain temperature, the performance improvement effect on the lithium iron phosphate was no longer obvious. Considering the cost and lithium replenishment effect, the comprehensive effect was better when the lithium replenishment temperature was 100°C.

[0188] In Example 1 and Examples 35 to 47, only the lithium replenishment time was changed. It was found that as the lithium replenishment time increased, the performance of the lithium iron phosphate after lithium replenishment increased. After a certain time, the performance improvement effect on the lithium iron phosphate was no longer obvious. Considering the cost and lithium replenishment effect, the comprehensive effect was better when the lithium replenishment temperature was 4h.

[0189] In Example 1 and Examples 48 to 53, only the solid-liquid ratio 1 of the lithium iron phosphate and lithium oxalate solution during lithium supplementation was changed. It was found that as the solid-liquid ratio 1 increased, the performance of the lithium iron phosphate after lithium supplementation did not change much. After reaching a certain ratio, the performance of the lithium iron phosphate decreased when the ratio increased again. Considering the cost and lithium supplementation effect, the comprehensive effect was better when the solid-liquid ratio 1 was 0.2 g / mL.

[0190] In Example 1 and Examples 54 to 63, only the type of polymer monomer was changed, and it was found that the coating effects of different polymer monomers were different; when the polymer monomer was tannic acid, the comprehensive effect was better;

[0191] In Example 1 and Examples 64 to 69, only the concentration of the polymer monomer was changed. It was found that as the concentration increased, the performance of the obtained lithium iron phosphate increased; after reaching a certain concentration, the performance of the lithium iron phosphate decreased when the concentration increased again; therefore, the comprehensive effect was better when the concentration of the polymer monomer was 5 g / L;

[0192] In Example 1 and Examples 70 to 75, only the solid-liquid ratio 2 of the lithium iron phosphate and the polymer monomer solution after lithium supplementation was changed. It was found that as the solid-liquid ratio 2 increased, the performance of the obtained lithium iron phosphate decreased; therefore, the comprehensive effect was better when the solid-liquid ratio 2 of the lithium iron phosphate and the polymer monomer solution after lithium supplementation was 0.1 g / mL;

[0193] In Example 1 and Examples 76 to 84, only the stirring time of the lithium iron phosphate and polymer monomer solution after lithium supplementation was changed. It was found that as the stirring time increased, the performance of the obtained lithium iron phosphate increased. After reaching a certain stirring time, further increasing the stirring time had no obvious effect on the performance improvement of the lithium iron phosphate. Therefore, the comprehensive effect was better when the stirring time was 15 minutes.

[0194] In Example 1 and Examples 85 to 94, only the heat treatment temperature was changed. It was found that as the heat treatment temperature increased, the performance of the obtained lithium iron phosphate increased, and after reaching a certain temperature, the performance of the lithium iron phosphate decreased when the temperature was further increased; therefore, the comprehensive effect was better when the heat treatment temperature was 600°C;

[0195] In Example 1 and Examples 95 to 102, only the heat treatment atmosphere was changed, and it was found that the performance of lithium iron phosphate obtained under different atmospheres was not much different; the comprehensive effect was better when the heat treatment atmosphere was argon;

[0196] In Example 1 and Examples 103 to 111, only the heat treatment time was changed. It was found that as the heat treatment time was prolonged, the performance of the obtained lithium iron phosphate increased, and the performance of the lithium iron phosphate did not change much after reaching a certain temperature. Considering the repair effect and cost, the comprehensive effect was better when the heat treatment time was 4 hours.

[0197] Comparison between Example 1 and Examples 112 to 113 shows that if the oxalic acid source and lithium source initially added can eventually generate lithium oxalate, the repair effect on waste lithium iron phosphate is equivalent to adding lithium oxalate;

[0198] Compared with Comparative Example 1, Example 1 exhibits a higher reversible discharge capacity at 5C and 10C rates, indicating that the lithium iron phosphate provided in the embodiment of the present invention is suitable for high-rate working conditions;

[0199] Compared with Comparative Example 2, Example 1 exhibits a higher reversible discharge capacity at different rates, indicating that the embodiment of the present invention provides an effective method for repairing waste lithium iron phosphate;

[0200] Comparison of Comparative Example 3 with Example 1 and Comparative Example 2 shows the effectiveness of lithium oxalate supplementation;

[0201] Comparison of Comparative Example 4 with Example 1 and Comparative Example 2 shows the effectiveness of heat treatment in improving the performance of waste lithium iron phosphate;

[0202] Comparison of Comparative Example 5 with Example 1 and Comparative Example 2 shows that lithium oxalate supplementation and surface coating can improve the performance of waste lithium iron phosphate to a certain extent;

[0203] Comparison of Comparative Example 6 with Example 1 and Comparative Example 2 shows that lithium oxalate supplementation and heat treatment can improve the performance of waste lithium iron phosphate to a certain extent;

[0204] Comparison of Comparative Example 7 with Example 1 and Comparative Example 2 shows that polymer surface coating and heat treatment improve the performance of waste lithium iron phosphate to a certain extent;

[0205] Comparison of Comparative Examples 2 to 7 with Example 1 shows that the synergistic effect of lithium oxalate supplementation, surface polymer small molecule monomer coating and heat treatment has the best repair effect on waste lithium iron phosphate.

[0206] Figure 3 It is a comparison diagram of the rate performance of Example 1 of the present invention and Comparative Example 1; Figure 4 The cycle performance of the lithium iron phosphate material obtained in Example 1 of the present invention at 5C and 10C rates. Figure 3 and Figure 4 It can be seen that compared with Comparative Example 1, the material of Example 1 exhibits higher reversible discharge capacity at 5C and 10C rates, indicating that the lithium iron phosphate provided in the embodiment of the present invention is more suitable for working at a high rate state and has good high rate performance.

[0207] In summary, the present invention realizes direct recovery of waste lithium iron phosphate through three steps of hydrothermal lithium replenishment, polymerization coating and heat treatment; firstly, waste lithium iron phosphate is hydrothermally replenished with lithium using a reducing agent and a lithium source, and then a polymer monomer with a specific structure is used as a carbon source, and its polymerization characteristics are utilized to polymerize on the surface of the material to form a uniform polymer coating layer, and finally, through a heat treatment process, further repair of the lithium iron phosphate crystal phase and uniform surface carbon layer coating are achieved, thereby completing the recovery and repair, and the recycled and repaired lithium iron phosphate material has high capacity and high rate performance.

Claims

1. A method for repairing waste lithium iron phosphate, characterized in that: The following steps are involved: S1, subjecting a mixture containing waste lithium iron phosphate, a reducing agent, a lithium source and water to a hydrothermal reaction to obtain a precursor A; S2, mixing the precursor A with a polymer monomer solution, allowing the polymer monomer to undergo polymerization and coating, forming a polymer coating layer on the surface of the precursor A, and obtaining a precursor B; the polymer monomer comprises at least one of a polyphenol monomer, a sulfur-containing heterocyclic acid monomer, or a carbon-carbon double bond-containing monomer; S3, heat-treating the precursor B in an atmosphere of protective gas to obtain a repaired lithium iron phosphate material.

2. The repair method according to claim 1, characterized in that: In step S1, the reducing agent includes at least one of a formic acid source, an oxalic acid source, thiourea or a carboxylic acid derivative; And / or, the lithium source includes at least one of lithium oxalate, lithium hydroxide, lithium carbonate, lithium chloride, lithium nitrate, lithium sulfate, lithium formate, lithium phosphate, lithium acetate, lithium metaphosphate or lithium borate.

3. The repair method according to claim 2, characterized in that: In step S1, the oxalic acid source in the reducing agent includes at least one of oxalic acid, lithium oxalate, lithium hydrogen oxalate, sodium oxalate, sodium hydrogen oxalate, potassium oxalate, potassium hydrogen oxalate, ferrous oxalate, ammonium oxalate, ferric oxalate or hydrates of the above compounds.

4. The repair method according to claim 1, characterized in that: In step S1, the ratio of the waste lithium iron phosphate to water is a first solid-liquid ratio, and the first solid-liquid ratio is 0.01 to 15 g / mL; and / or, the reducing agent concentration in the mixture is 0.05 to 20 mol / L; and / or, the lithium ion concentration in the mixture is 0.1 to 40 mol / L; And / or, the temperature of the hydrothermal reaction is 30 to 300° C.; And / or, the hydrothermal reaction time is 0.5 to 200 hours.

5. The repair method according to claim 1, characterized in that: In step S2, the polyphenol monomers include diphenol monomers, pyrogallol monomers or a combination thereof; and / or, the sulfur-containing heterocyclic acid monomer is selected from dithiolane-containing acid monomers; And / or, the carbon-carbon double bond-containing monomer includes at least one of acrylic acid monomers, acrylonitrile monomers, acrylamide monomers, and vinyl monomers.

6. The repair method according to claim 5, characterized in that: In step S2, the polyphenol monomer includes at least one of dopamine, dopamine hydrochloride, catechol, catechin, ellagic acid, gallic acid, tannic acid or anthocyanin; and / or, the sulfur-containing heterocyclic acid monomer includes α-lipoic acid, asparagus acid or a combination thereof; And / or, the carbon-carbon double bond-containing monomer includes at least one of ethylene glycol methacrylate, acetoacetate, 2-cyanoethyl acrylate, 2-cyanoacrylic acid, 2-cyanoacrylate propyl, hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, acrylonitrile, N-isopropylacrylamide, N,N'-methylenebisacrylamide, 2-vinylpyridine, 3-vinylpyridine, 4-vinylpyridine, N-vinylformamide or N-vinylacetamide.

7. The repair method according to claim 1, characterized in that: In step S2, the concentration of the polymer monomer solution is 0.05 to 15 g / L; And / or, the amount ratio of the precursor A to the polymer monomer solution is a second solid-liquid ratio, and the second solid-liquid ratio is 0.005-15 g / mL; and / or, the time for mixing the precursor A and the polymer monomer solution is 0.5 to 80 minutes; And / or, the average thickness of the polymer coating layer is ≤20 nm.

8. The repair method according to claim 1, characterized in that: In step S3, the protective gas includes an inert gas, a reducing gas or a combination thereof; And / or, the temperature of the heat treatment is 200-900°C; And / or, the heat treatment holding time is 0.5 to 15 hours.

9. A lithium iron phosphate material obtained by the repair method according to any one of claims 1 to 8.

10. The lithium iron phosphate material according to claim 9, characterized in that: The lithium iron phosphate material comprises lithium iron phosphate particles and a carbon coating layer coated on at least a portion of the surface of the lithium iron phosphate particles; the average thickness of the carbon coating layer is ≤15 nm.

11. Use of the lithium iron phosphate material according to claim 9 or 10 in preparing lithium ion batteries.

Citation Information

Cited By

  • Method for regenerating lithium iron manganese phosphate positive electrode material and application of lithium iron manganese phosphate positive electrode material

    CN121376937A

  • Lithium iron phosphate positive electrode material and repairing method and application thereof

    CN122456001A